Impact of Personal Characteristics of Farmers on Cocoa Yields: Case of Centre Region, Mbangassina Municipality, Cameroon - Herve Bertrand Yakan; Ehabe Eugene; Vanisa Yenwo Nonzienwo (Indonesian Coffee and Cocoa Research Institute, 2020)
Cameroon is the fifth largest cocoa producer in the world with approximately 220,000 tons of cocoa produced annually. Many factors account for thisproductivity, amongst which are ageing farms and personal characteristics of farmers. The study follows a hypothetico-deductive methodology through whicha random sampling technique was adopted and relevant primary data was gathered with the aid of a structured questionnaire administered to 150 cocoa farmers from5 villages; Talba, Biakoa, Goura II, Mbangassina, and Bilomo. Correlation analysis and ordinary least squares regression were used to examine the relationship andeffects between socio-economic variables and cocoa yields. Findings showed a positive correlation between the socio-economic variables and cocoa yields, socioeconomic factors such as experience in cocoa farming, number of farms, source of labour, farm size, income were statistically significant at p = 1%, 5%, and 10%. Personal characteristics such as farm size, farming experience, percentage of income from cocoa farming, source of labour, number of farms per cocoa farmer,and cocoa price had a significant impact on cocoa yields. However, personal characteristics such as age, sex, marital status and household size did not showany significant impact on cocoa yields. Thus, professionalizing cocoa farmers and training of farmers in good cocoa business practices can go a long way toimprove cocoa productivity.